A intertextualidade nas tiras de Armandinho: uma proposta de leitura por meio da linguística textual - Testa, Danilo Baptista (2025)
The inclusion of comic strips in the school environment, motivated by the National Curriculum Parameters (PCN) and reaffirmed by the National Common Curricular Base (BNCC), has posed new challenges for teachers, highlighting the need for a deeper understanding of their language and resources. In this context, the Armandinho comic strips, created by Alexandre Beck, stand out for addressing, in an accessible yet profound way, themes related to childhood, society, and human values. This research, developed within the research line "Reading, Writing, and Teaching of Portuguese Language" of the Graduate Program in Portuguese Language at the Pontifical Catholic University of São Paulo, focuses on developing an intertextual reading approach for Armandinho strips. The study is based on the observation that many students face difficulties in interpreting textual genres that combine verbal and visual codes, a problem exacerbated by the lack of adequate strategies from elementary school teachers. Therefore, the study aims to investigate the importance of intertextuality for understanding comic strips and to propose pedagogical practices that promote critical and autonomous reading. In dialogue with the principles of Textual Linguistics (KOCH, 2015, 2018, 2019; CAVALCANTE et al., 2022; RAMOS, 2017, 2019), the research adopts a theoretical-propositional approach and culminates in the creation of a didactic sequence focused on intertextuality and the articulation between verbal and visual elements in the Armandinho strips